34. CLINICAL AND PARACLINICAL CHARACTERISTICS OF GASTROINTESTINAL BLEEDING IN PATIENTS WITH GASTRIC AND DUODENAL ULCERS AT NGHE AN GENERAL FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe the clinical and paraclinical characteristics of patients with gastrointestinal bleeding due to peptic ulcers at Nghe An General Hospital in 2023.Research Methods: Cross-sectional descriptive study with analysis.Results: Study of 70 patients diagnosed with gastrointestinal bleeding due to peptic ulcer treated at the Department of Internal Medicine, Nghe An General Hospital. Information was collected by examination and pre-designed medical records. Results: Male/female ratio was 2.2/1; Average age was 56.6±16.6, highest in the 50-69 age group 50%. Patients with concomitant chronic diseases were 4.4 times higher than those without concomitant chronic diseases, of which the most common were polyarthritis and osteoarthritis. Clinical symptoms of the disease were mainly black stools, vomiting blood; 5.7% of cases had recurrent gastrointestinal bleeding. Hemoglobin and red blood cells decreased to a moderate level. Endoscopy of the duodenal ulcer site had the highest incidence; mainly 1 ulcer with the highest rate of 84.3%.Conclusion: Gastrointestinal bleeding due to gastric and duodenal ulcers is a common medical and surgical emergency. Timely diagnosis and treatment intervention reduces mortality, recurrent bleeding, blood transfusion, hospital stay and treatment costs. Symptoms of black stools and vomiting blood always account for a high rate in cases of gastrointestinal bleeding due to gastric and duodenal ulcers. Common symptoms can appear at the same time and are typical symptoms that cause patients to be hospitalized.
Keywords: Gastrointestinal bleeding due to gastric and duodenal ulcers; gastrointestinal bleeding.